Silent Fistula of the Ascending Aorta to Pericardium by Brucella Endocarditis - Sabzi, Feridoun (J Cardiovasc Thorac Res, 2015)
We report the case of a 26-year-old male patient with 2-week history of Brucella aortic valve endocarditis that was referred from general hospital to our hospital emergency room with pallor of the skin and mucous membranes accompanied by systemic hypotension and chest pain. Trans esophageal echocardiography (TEE) revealed a 30-mm ascending aorta at the pulmonary trunk with no evidence of the false lumen or intimal flap. TEE also showed a large vegetation of the aortic valve that limited to noncoronary sinus with moderate pericardial effusion. TEE did not showed fistula tract of nonaortic coronary sinus ring to intra mural of aorta and to pericardial cavity. The patient underwent open heart surgery with resection of destructed aortic valve and vegetation and replacement of aortic valve with prosthetic valve (Carbomedics, Sorin group. 23 mm sizes) with separated pledged suture. Debridement of aortic intra mural fistula tract and its replacement with fresh pericardial patch than performed. The pericardial cavity had moderate bloody effusion. The patient recovered uneventfully and was discharged in the 15th postoperative day. In this case, we report a rare silent clinical presentation of aortic wall fistula by vegetation and aortic ring abscess and periaortic wall hematoma, and reviewed its medical and surgical treatment.